Lifestyle-, environmental-, and additional health factors associated with an increased sperm DNA fragmentation: a systematic review and meta-analysis - Anett Szabó; Szilárd Váncsa; Péter Hegyi; Alex Váradi; Attila Forintos; Teodóra Filipov; Júlia Ács; Nándor Ács; Tibor Szarvas; Péter Nyirády; Zsolt Kopa (Reproductive Biology and Endocrinology)
Abstract Introduction Infertility affects one in every six couples in developed countries, and approximately 50% is of male origin. In 2021, sperm DNA fragmentation (SDF) testing became an evidence-based test for fertility evaluations depicting fertility more clearly than standard semen parameters. Therefore, we aimed to summarize the potential prognostic factors of a higher SDF. Methods We conducted a systematic search in three medical databases and included studies investigating any risk factors for SDF values. We calculated mean differences (MD) in SDF with 95% confidence interval (CI) for exposed and non-exposed individuals. Results We included 190 studies in our analysis. In the group of associated health conditions, varicocele (MD = 13.62%, CI: 9.39–17.84) and impaired glucose tolerance (MD = 13.75%, CI: 6.99–20.51) had the most significant increase in SDF. Among malignancies, testicular tumors had the highest impact, with a maximum of MD = 11.3% (CI: 7.84–14.76). Among infections, the overall effects of both Chlamydia and HPV were negligible. Of lifestyle factors, smoking had the most disruptive effect on SDF – an increase of 9.19% (CI: 4.33–14.06). Different periods of sexual abstinence did not show significant variations in SDF values. Age seemed to have a more drastic effect on SDF from age 50 onwards, with a mean difference of 12.58% (CI: 7.31–17.86). Pollution also had a detrimental effect – 9.68% (CI: 6.85–12.52). Conclusion Of the above risk factors, varicocele, impaired glucose tolerance, testicular tumors, smoking, pollution, and paternal age of over 50 were associated with the highest SDF. Trial registration CRD42021282533.